If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6(3x + -4) = -2(7x + -4) + -12 Reorder the terms: 5x + -6(-4 + 3x) = -2(7x + -4) + -12 5x + (-4 * -6 + 3x * -6) = -2(7x + -4) + -12 5x + (24 + -18x) = -2(7x + -4) + -12 Reorder the terms: 24 + 5x + -18x = -2(7x + -4) + -12 Combine like terms: 5x + -18x = -13x 24 + -13x = -2(7x + -4) + -12 Reorder the terms: 24 + -13x = -2(-4 + 7x) + -12 24 + -13x = (-4 * -2 + 7x * -2) + -12 24 + -13x = (8 + -14x) + -12 Reorder the terms: 24 + -13x = 8 + -12 + -14x Combine like terms: 8 + -12 = -4 24 + -13x = -4 + -14x Solving 24 + -13x = -4 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. 24 + -13x + 14x = -4 + -14x + 14x Combine like terms: -13x + 14x = 1x 24 + 1x = -4 + -14x + 14x Combine like terms: -14x + 14x = 0 24 + 1x = -4 + 0 24 + 1x = -4 Add '-24' to each side of the equation. 24 + -24 + 1x = -4 + -24 Combine like terms: 24 + -24 = 0 0 + 1x = -4 + -24 1x = -4 + -24 Combine like terms: -4 + -24 = -28 1x = -28 Divide each side by '1'. x = -28 Simplifying x = -28
| 9+3g+8g+-6+-3g= | | (-4-5)=5(-4)-14 | | -n^2=-33 | | 5x^2-38=187 | | 6m-20=28 | | Y=-2+-8x | | 5+8=42 | | 10x+13=3(3x+6) | | 6=14m | | 56-5=51 | | -4x-5(-4+4x)=60 | | r=1/5=4/7 | | 5a+6=2a+29 | | X+8y+-6y+3y+18= | | (x-5)=5x-14 | | 8=n+8-4n | | 3x-26=5x-6 | | 105=p*7 | | 4x(8-4)+9=20 | | 9(6x-2)=90 | | n-300=7.29 | | 48x^2-20-12=0 | | 3n+3=-99 | | 5x+-4+7x+-12+-8x= | | 32/x=1.6 | | 8=32.8b | | ((6x10^2)(3x10^9)(3x^10^13))/(6x10^10) | | 1×(-4)-8×9/-3 | | 9.5=2n-23 | | 42x+28yingcf= | | 2x^2+9k=-7 | | X-5=-5-x |